MULTIDISCIPLINARY TRANSFORMATIVE LEARNING PRACTICE IN INDONESIAN CONTEXT - Agustina, Noni; Anindita, Rina; Sitoayu, Laras; Hardianti, Hardianti; Cinantya, Ixora Gupita; Mustaqim, Karna; Firmasyah, Ezik (Universitas PGRI Sumatera Barat, 2024)
Analytical thinking, creative thinking, resilience, flexibility, agility, motivation, self-awareness, and a lifelong learning mindset are the top five skills out of twenty-six are crucial for the workforce. These skills are highly important to be developed in higher education through transformative learning that encourages students to broaden their perspectives or change their mindset. Previous researches investigated the transformative learning, however there is still scarce study on the practice of transformative learning in a multidisciplinary context in higher education. Therefore, this study aims to explore the practice of transformative learning across different discipline. Narrative inquire research design was employed by involving six educators teaching at a private university in Jakarta, Indonesia. Classroom observation and interview was carried to collect the data. The finding showed that practice of transformative learning included critical self-reflection and dialogic conversation. The transformative learning provided the impact for the students.